2008
DOI: 10.1007/s00280-008-0809-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of aged garlic extract (AGE) on the apoptosis of intestinal epithelial cells caused by methotrexate

Abstract: The MTX-induced apoptosis of IEC-6 cells was shown to be depressed by AGE. AGE may be useful for the cancer chemotherapy with MTX, since AGE reduces the MTX-induced intestinal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Caspase-3, the main downstream effector, cleaves the majority of cellular substrates in apoptotic cells (21,35). Several studies showed that caspase-3 activity was increased in the process of intestinal apoptosis during chemotherapy, including 5-FU treatment (5,25,44). We observed a marked increase in immunopositive cells for cleaved caspase-3, the active form of caspase-3, which localized to the intestinal crypt in a manner consistent with the localization of apoptotic cells in WT mice.…”
Section: Discussionsupporting
confidence: 51%
“…Caspase-3, the main downstream effector, cleaves the majority of cellular substrates in apoptotic cells (21,35). Several studies showed that caspase-3 activity was increased in the process of intestinal apoptosis during chemotherapy, including 5-FU treatment (5,25,44). We observed a marked increase in immunopositive cells for cleaved caspase-3, the active form of caspase-3, which localized to the intestinal crypt in a manner consistent with the localization of apoptotic cells in WT mice.…”
Section: Discussionsupporting
confidence: 51%
“…Gao and Horie [3] showed that MTX inhibits the de novo purine synthesis and thymidine kinase in the salvage pathway of pyrimidine synthesis in crypt cells of the small intestine, leading to villous degeneration. Li et al [12] reported that MTX treatment increases the cell death and decreases cell number in the intestinal epithelium. In our study, MTX treatment was associated with damage to intestinal tissue in the form of villous shortening, epithelial atrophy, crypt loss, inflammatory cells infiltration in the lamina propria and goblet cell loss .…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, certain natural products have protective effects against apoptosis. Ginkgo biloba extract protected rat pheochromocytoma (PC12) cells from possible oxidative damage induced by trophic factors and garlic extracts are also protective against the apoptosis of intestinal epithelial cells caused by methotrexate (28,29). Therefore, the effect of natural products on mitochondrial function remains controversial.…”
Section: Discussionmentioning
confidence: 99%